Cellular, Histologic, and Molecular Changes Associated With Endometriosis and Ovarian Cancer - Siufi Neto, João; Kho, Rosanne M.; dos Santos Siufi, Daniela Freitas; Baracat, Edmund Chada; Anderson, Karen S.; Abrão, Maurício Simões (Elsevier, 2014)
Our understanding of the pathogenesis of endometriosis is rapidly evolving as early molecular events are increasingly identified. Endometriosis is associated with increased risk of ovarian cancer and exhibits neoplastic phenotypes including invasion of stromal tissue and lymphatic spread to distant organs. This review of the literature establishes the clinical, epidemiologic, and pathologic correlation between endometriosis and low-grade ovarian cancer. Genetic studies have demonstrated that endometriotic lesions have mutations in genes directly related to neoplasms, in particular the p53, KRAS, PTEN, and ARID1A genes, which suggests a direct transition from a subset of endometriotic lesions to invasive carcinomas. The identification of both genetic and epigenetic biomarkers including microRNAs are essential for identifying patients at risk for the transition to neoplasia. © 2014 AAGL.
Keywords: Endometriosis; MicroRNA; Molecular alterations; Ovarian cancer